Peningkatan Kompetensi Penyusunan Dokumen Petty Cash dalam Mempersiapkan Uji Kompetensi Keahlian pada Siswa SMK Muhammadiyah Adiwerna - Fitri Amaliyah; Dewi Kartika; Aryanto Aryanto (Jurnal Surya Masyarakat, 2025)
Petty cash is one of the important aspects of daily financial management. Proper cash management will help companies in handling routine expenses that are urgent and of relatively small value. The problem that occurs at SMK Muhammadiyah Adiwerna is that students do not understand about the recording of petty cash, especially the difference in the imprest method and fluctuations because in the independent curriculum the petty cash material is getting less and less and usually the cases given to students are in the form of the imprest method only. The implementation method is divided into three stages, namely identifying problems, implementing activities, and evaluating results. In the first stage, the PKM team conducted a survey and interview with the Head of SMK Muhammadiyah Adiwerna. The second stage, namely the implementation of activities, is carried out by giving lectures, tutorials and discussions. The final stage is evaluation, carried out by providing pretest and posttest to all PKM participants. Based on the results of the presentation of the material delivered by the lecturer team about recording petty cash documents using the impression and fluctuation method, it gave results, namely all participants were able to follow the flow of material guided by the lecturer team and could do the practice of compiling journals into cash payment journals and petty cash books well. The training that has been carried out shows that there is an improvement in students' skills about recording petty cash documents using the imprest and fluctuation method method for students of SMK Muhammdiyah Adiwerna Tegal to prepare to take the Expertise Competency Test.